Implementation of Dijkstra's Algorithm to Determine Evacuation Paths in Earthquake and Tsunami Simulations in Bengkulu City Based on Gis - Yulia Darmi; Muntahanah Muntahanah (Jurnal Media Computer Science, 2022)
judging from the geographical location, bengkulu province is a province where there are quite a lot of cracks in the earth's plate, it has the potential to occur tectonic earthquakes that can cause earthquakes and tsunamis. the natural vulnerabilities that exist make almost the entire west coast of bengkulu including bengkulu city very prone to earthquakes and tsunamis. in the event of an earthquake and tsunami, if disaster management and evacuation routes are not prepared, it will cause damage to buildings and can result in very severe casualties such as the events in aceh & lombok. under these conditions, it is necessary to carry out an evacuation that aims to save the population from the danger of a tsunami, from a place that is considered safe. the thing that is most closely related to evacuation is time, the longer the evacuation process or the greater the evacuation time required, the more lives will be threatened. in the evacuation process it takes a fast time to reach the gathering point or the nearest point. one of the closest/shortest paths is found in dijkstra's algorithm, in addition to using the dijkstra algorithm to reach the shortest destination location, a geographic information system is used which presents a map of the location of the destination to be achieved. geographic information system (gis) is an information system used to process data on earthquake and tsunami evacuation routes in the city of bengkulu. an android-based geographic information system will greatly assist the community in solving these problems, thus we can see the closest evacuation routes that must be passed, this study aims to utilize dijkstra's algorithm to determine earthquake and tsunami evacuation routes so that it can effectively assist in the evacuation process when an earthquake and tsunami occurs and create an information system application for earthquake and tsunami evacuation routes. keywords : dijkstra, geographic information system, evacuation, path, gathering point and hazard point